Launch your career in college : strategies for students, educators, and parents - Scheele, Adele M. (Praeger Publishers, 2005)
Adele Scheele, a widely published career strategist, has created a roadmap designed to inspire students to use their time wisely, to help their parents become better coaches to their children, and to empower college faculty and administrators to become more active mentors.